PENGARUH ENTERPRISE RISK MANAGEMENT, PROFITABILITAS DAN KEPEMILIKAN MANAGERIAL TERHADAP NILAI PERUSAHAAN ASURANSI DI BURSA EFEK INDONESIA - Juli Ismanto; Iin Rosini; Nofryanti (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
This study aims to determine the impact of corporate risk management disclosure, profitability, and managerial ownership on firm value. Secondary data comes from the financial statements of insurance companies listed on the IDX between 2016 and 2021. Sixteen companies were used as research objects for six years of observation, resulting in 96 observations. This study used panel data regression analysis using Eviews12 data processing as the mechanism. The research findings show that enterprise risk management and managerial ownership do not affect firm value. On the other hand, profitability proxied by ROA has a significant and negative influence on firm value. Therefore, it can be concluded that profitability significantly affects firm value, with a negative coefficient indicating that low ROA means declining profits, reduced competitiveness, inadequate capital, and future business turmoil.